Grundtvigs vej til Saxo - Lundgreen-Nielsen, Flemming (Grundtvig-Studier, 2017)
This article documents Grundtvig’s path to the works of Saxo Grammaticus from around 1787, when he was taught to read by his strongwilled mother, and until departure from Saxo after completing his translation of Saxo’s chronicle in 1823. An overview of this period focuses on the significant dates, book titles, and other points of interest that mark his interest in the medieval clerical scribe’s work. Attention then turns to the fact that, after 1823, Grundtvig never seriously returned to study of Saxo’s ideas, nor did he ever try to reproduce his silver age Roman style in the Danish language. For a very short while, Grundtvig thought about but never followed through on a continuation of a history of Denmark from where Saxo stopped (viz. in 1186). Though Grundtvig’s preoccupation with Saxo lasted for the rest of his life, he preferred the Icelandic tongue instead of Latin and believed that Norse mythology was a more fertile field than Latin for discoveries about the national history of the Danes. The present survey of these key points in how Grundtvig viewed and evaluated Saxo also supplements previous scholarly treatments of stylisticlinguistic analyses of Grundtvig’s youth translation of Saxo.